Differences in tissue distribution ability of evodiamine and dehydroevodiamine are due to the dihedral angle of the molecule stereo-structure - Luo, Jie; Wen, Wen; Chen, Jie; Zeng, Xiaobo; Wang, Ping; Xu, Shijun (Frontiers in Pharmacology, 2023)
This researcher focused at the evodiamine and dehydroevodiamine tissue distribution and structure-pharmacokinetics (PK) relationship after intravenous injection in mice. Using a transmembrane transport experiment, the permeability of evodiamine and dehydroevodiamine on Caco-2 cells was evaluated. The tissue distribution and pharmacokinetics (PK) of evodiamine and dehydroevodiamine in mice were studied. To comprehend the connection between structure and tissue distribution, physicochemical property evaluations and molecular electrostatic potential (MEP) calculations were performed. Dehydroevodiamine's Papp values in vitro were 10-5 cm/s, whereas evodiamine's were 10-6 cm/s. At a dose of 5 mg/kg, the brain concentration of dehydroevodiamine was 6.44 times more than that of evodiamine. By MEP or physicochemical measures, the permeability difference between evodiamine and dehydroevodiamine is unaffected.The dihedral angle of the stereo-structure appears to be the main cause of the difference in tissue distribution ability between evodiamine and dehydroevodiamine. Dehydroevodiamine has a dihedral angle of 3.71° compared to 82.34° for evodiamine. Dehydroevodiamine can more easily pass through the phospholipid bilayer than evodiamine because it has a more planar stereo-structure. Dehydroevodiamine is therefore more likely to pass cross the blood-brain barrier and enter the brain in a tissue-specific manner.